2011
DOI: 10.1063/1.3574908
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionation and comproportionation reactions of resistive switching in polycrystalline NiOx films

Abstract: Articles you may be interested inNickel vacancy behavior in the electrical conductance of nonstoichiometric nickel oxide film Reproducible resistive switching in nonstoichiometric nickel oxide films grown by rf reactive sputtering for resistive random access memory applications NiO x thin film exhibited excellent bistable unipolar resistive switching ͑RS͒, which has a high potential in nanoscale nonvolatile-memory applications. The underlying reaction of RS in NiO x is still in debate. We studied the chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…30 These Ni ions result from breaking of Ni bonds 45,48 in the Ni filaments, and the O ions result from the thermal decomposition effect of surrounding oxygen-rich clusters such as Ni 2 O 3 produced in the SET process. 24,44 On the basis of the preceding scenario for the RESET process, we can explain the strong correlation between sign of the AMR ratio and RRR value of the HRS as follows. We have shown that the size of Ni filament in NiO films varies over a large range in this work, and it was reported in the literature that higher temperature due to Joule heating is needed to reset the Ni conducting filaments with relatively large diameters.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…30 These Ni ions result from breaking of Ni bonds 45,48 in the Ni filaments, and the O ions result from the thermal decomposition effect of surrounding oxygen-rich clusters such as Ni 2 O 3 produced in the SET process. 24,44 On the basis of the preceding scenario for the RESET process, we can explain the strong correlation between sign of the AMR ratio and RRR value of the HRS as follows. We have shown that the size of Ni filament in NiO films varies over a large range in this work, and it was reported in the literature that higher temperature due to Joule heating is needed to reset the Ni conducting filaments with relatively large diameters.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…47 Therefore, the migration of Ni ions during the RESET process should be considered, which has been neglected in previous work. 23,24,44 We propose the following scenario for the RESET process. The current through Ni filaments leads to Joule heating, which makes Ni ions migrate out of the hot region (Ni filaments) and oxygen ions migrate in the reverse direction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper concerns two opposite processes involved with redox reactions, named as disproportionation [1] (dismutation [2]), and symproportionation [3][4][5] (also known as synproportionation [6], conproportionation [7][8][9][10] comproportionation [11,12]) reactions, see [13]. The adjective "proportionate" means "being in proper proportion", or "degree when considered in relation to something else" [14].…”
Section: Introductionmentioning
confidence: 99%
“…[21] However, in the case of Ni oxides, this peak has also been assigned to the emission from the Ni2O3 phase that can be present at low concentration within the NiO films. [25] A possible contribution from a Ni2O3 phase in the Ni 2p3/2 spectrum is difficult to distinguish within the signal dominated with NiO phase, as the BE of Ni-O bonds in Ni2O3 overlap with the multiplet splitting structure of NiO (peak 3 from Figure 2). [15,26] Although in the present paper we only discuss the formation of a NiO phase, the presence of a small concentration of Ni2O3 phase should also be anticipated within the total concentration of Ni oxide.…”
Section: Doi: 105562/cca3149mentioning
confidence: 99%